Correlation Between Toddler Care and Nutrition Status - Hidayati, Irul; Andyarini, Esti Novi (International Conference on Sustainable Health Promotion, 2018)
Nutritional Status is one of the indicators of children's health. During the five years (infancy) is an important period where the child needs nutritional adequacy to support his physical growth. Children are dependent on the mother role in parenting and childcare. This research aimed to find out the correlation of toddler care consists of feeding practices, psychosocial stimulation and health care with nutritional status. Observational research is analytic with a cross-sectional design. The research was carried out in the Porong subdistrict of Sidoarjo Regency, East Java on October 2017. The sample in this research are some of the mothers who have toddlers in the Porong subdistrict of Sidoarjo Regency totaled 72 people by using simple random sampling technique. Data analysis using Fisher's Exact test with a confidence level of 95%. Results: most (86.1%) toddler have normal nutrition status, and 13.9% toddler has a status of malnutrition. Most of the feeding practices (86.1%) are appropriate, 13.9% are not appropriate. Psychosocial stimulation majority (83.3%) is good and 16.7% psychosocial stimulation is not good. Healthcare majority (91.7%) is good and 8.3% not good. As the result there is a relationship of feeding practices with toddler nutritional status (p = 0.03), there is psychosocial stimulation relationship with nutritional status toddler (p = 0.01), there is no health-care relationship with nutritional status toddler (p = 0,418).